Bleeding complications during percutaneous endoscopic gastrostomy treated with hemoclips - González González, José Alberto; Giasi Gonzalez, Eduardo; Bosques Padilla, Francisco Javier; Gaytán Torres, Juan Obed; Maldonado Garza, Héctor Jesús; Hernández Juárez, Iliana Aracely (UANL. Facultad de Medicina, 2009)
Percutaneous endoscopic gastrostomy (PEG) has become the primary procedure for the long-term nutrition of patients with swallowing disorders. It has been shown to be a safe method with a lower complication rate than surgical placement. Acute hemorrhage following PEG is rarely reported. We present a case report about the use of hemoclips to stop bleeding from gastric wall vessel injury during a PEG procedure.